The Impact of Varying Sinks on Load Distribution in IoT Routing Under Static and Mobile Scenarios - Al-Qassas, Raad S. (Recent Advances in Computer Science and Communications, 2021)
Background: The majority of routing algorithms proposed for IoT can be categorized under modifications in routing protocols designated for IoT such as RPL objective functions enhancements, while others are enhancements in routing algorithms derived from those which were designed for ad hoc networks. We have thoroughly investigated the literature on these modifications or enhancements. However, there is a lack of an in-depth study to examine the impact of varying number of sinks and nodes' mobility on routing algorithms based on MRHOF and OF0. Method: We examine the ability of MRHOF and OF0 in distributing the load with the impact of the varying number of sink nodes under static and mobile scenarios with the aid of COOJA simulator. This has been conducted using various metrics including regular metrics such as throughput and power consumption, and newly derived metrics including packets load deviation and power deviation which are derived for the purpose of measuring load distribution. Results: Increasing number of sinks has shown that OF0 outperforms MRHOF in terms of power consumption and power deviation under both static and mobile scenarios. On the other hand, in mobile scenarios, MRHOF outperforms OF0 in terms of packets load deviation for a high number of sinks. Conclusion: Both techniques demonstrated performance merits when challenged with varying number of sinks. Therefore, understanding their behaviour would play a key role in deriving an efficient load distribution technique, which is likely to be achieved by considering network conditions.
Keywords: Machine-to-Machine interaction